2021
DOI: 10.25122/jml-2020-0180
|View full text |Cite
|
Sign up to set email alerts
|

Fracture resistance of endodontically treated teeth restored with resin post reinforced with glass fiber

Abstract: This study aims to determine whether the design of resin posts reinforced with glass fiber (FRC) and Reporfost (Angelus, Londrina, PR, Brazil) significantly improves the fracture resistance of endodontically treated teeth restored through this method.A batch of 30 maxillary monoradicular teeth (15 central incisors, 15 canines) were treated endodontically by step-back technique (apical enlargement 40-K file) sealed with Sealapex (Kerr Corporation, Orange, US) and gutta-percha by lateral condensation, cold. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
7
0
2
Order By: Relevance
“…It has been reported that root dentin offers less favorable conditions for the adhesion of glass fiber-reinforced posts than coronal dentin due to various factors[ 10 ] such as the application method of luting material and post pretreatment. [ 1 11 , 12 ] Therefore, the importance of the present study lies in demonstrating whether surface conditioning of the glass fiber posts prior to silanization significantly increases the bond strength to the root canal. From the results obtained, it was evidenced that silanization, as the only pretreatment of glass fiber post, is enough to achieve optimal results, since silane, being a bifunctional molecule, is capable of forming a chemical bond with glass fiber and with the organic resin of luting material, favoring good bonding, and also explains its significant association with cohesive failure mode, showing good physical and chemical bonding between both materials, since the push out test showed bond fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that root dentin offers less favorable conditions for the adhesion of glass fiber-reinforced posts than coronal dentin due to various factors[ 10 ] such as the application method of luting material and post pretreatment. [ 1 11 , 12 ] Therefore, the importance of the present study lies in demonstrating whether surface conditioning of the glass fiber posts prior to silanization significantly increases the bond strength to the root canal. From the results obtained, it was evidenced that silanization, as the only pretreatment of glass fiber post, is enough to achieve optimal results, since silane, being a bifunctional molecule, is capable of forming a chemical bond with glass fiber and with the organic resin of luting material, favoring good bonding, and also explains its significant association with cohesive failure mode, showing good physical and chemical bonding between both materials, since the push out test showed bond fracture.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] There are several factors that may affect the retention of glass fiber-reinforced posts in root canals, such as the preparation and conditioning of post space, postcementation, type of endodontic cement, adhesive system to be used, method of application of luting agent, and post pretreatment. [ 1 11 , 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…The fracture resistance test can be performed in two ways, either by separating the crown from the root as in some studies [ 20 , 21 ] or by keeping the crowns together with the roots [ 22 , 23 ]. Crowns were preserved in this study for two reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high modulus of elasticity is usually associated with metal posts which helps them to transmit the stresses from these posts to the tooth structure resulting in the failure of the post system (Lamichhane et al, 2014). On the other hand, fiber posts provide improved fracture resistance and distribute stresses evenly, which is beneficial for the integrity of the remaining tooth structure (Chirila et al, 2021). For the restoration's success, forming a durable bond between the adhesive and post is crucial as it would provide increased resistance against variously directed forces.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, fiber posts provide improved fracture resistance and distribute stresses evenly, which is beneficial for the integrity of the remaining tooth structure (Chirila et al, 2021). For the restoration's success, forming a durable bond between the adhesive and post is crucial as it would provide increased resistance against variously directed forces.…”
Section: Introductionmentioning
confidence: 99%